Exploring the Relationship Between Shariah Education and National Identity in Nigeria’s Universities - Shittu, Abdulwahab Danladi; Mustapha, Sodiq Sunkanmi; Yakub, Abdul Waheed Olarewaju; Aniyan, Abdullateef Abdulazeez (Universitas Muhammadiyah Surakarta, 2025)
This study examines the intricate relationship between Shariah education and the formation of national identity within Nigerian universities. As a country marked by religious, ethnic, and cultural diversity, Nigeria faces ongoing challenges in forging a cohesive national identity. The inclusion of Shariah-related courses in university curricula, particularly in institutions located in the predominantly Muslim northern region, raises critical questions about the role of religious legal education in a secular and pluralistic state. Using a multidisciplinary methodology that combines legal analysis, educational policy review, and qualitative interviews with students and faculty, this research investigates how Shariah education influences perceptions of citizenship, national belonging, and social cohesion. Findings suggest that while Shariah instruction can serve as a means of cultural affirmation and moral guidance, it also has the potential to either bridge or deepen national divides depending on how it is framed and integrated within broader academic and civic discourses. The paper concludes with recommendations for a more inclusive educational framework that respects religious diversity while reinforcing a shared national identity.